PENGGUNAAN MEDIA SOSIAL SEBAGAI ALTERNATIF MEDIA PEMBELAJARAN ONLINE - Nindya Adiasti (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2021)
This study produces teaching materials that are posted on social media accounts that are used as alternative media for online learning media and to determine the responses of students at the University of Borneo Tarakan. The research used is the development research by Borg and Gall. The subjects of this study were 3rd semester students of the PGSD study program at the University of Borneo Tarakan. This research product in the form of images and videos posted on TikTok, Instagram, Facebook, and YouTube social media accounts. The results of the assessment of media experts obtained a percentage of 73%, material experts a percentage of 82%, and from linguists a percentage of 70%. Based on the results of this assessment, the teaching materials are declared valid and usable. The results of the small group trial obtained an average percentage of 81% with the category very satisfied and the results of the field trial obtained an average percentage of 82% also with the category very satisfied. It was stated that the media could be accepted by students. Taking into account the results of this research, it can be concluded that online teaching materials have been tested for feasibility, excellence, and can be used as an alternative media for online learning and learning processes.